Aplikasi Pupuk NPK untuk Meningkatkan Produksi Tanaman Kacang Tanah: Aplikasi Pupuk NPK untuk Meningkatkan Produksi Tanaman Kacang Tanah - Wuriesyliane wuriesyliane; Andri Saputro (J-Plantasimbiosa, 2021)
Peanut production both in Java and outside Java tends to fluctuate. Nuts have a high economic value and are one of the sources of protein in the diet of the Indonesian population. This study aims to determine the application of NPK fertilizer to peanut crop production. The study was conducted in Pangkalan Panji Village, Banyuasin III, in March-June 2021. This study was compiled using a one-factor Randomized Block Design (RAK) with four replications. The factors used consist of six levels, namely N0, N1, N2, N3, N4 and N5. The results showed that the application of NPK fertilizer had no significant effect on plant height and weight of peanut pods, while the parameters of number of pods, number of branches, weight of wet pods and weight of 100 grains showed a significant effect on NPK treatment of 300 kg/ha (50g/plot).